Myra Bradwell, All the Laws of the State of Illinois Passed by the General Assembly, Convened January 8th, 1879. Adjourned sine die May 31st, 1879. With Head Notes and References to the Revised Statutes of 1877 (Chicago, IL: Chicago Legal News Company, 1879), 156-157. Article XI General Provisions, § 5 Other Organizations Prohibited - (:unkn) unknown (General Publisher, 1879)
Prohibited any body of men to organize as a military company or organization, or to drill or parade with arms in any city, or town.
--
Keywords: MILITIAS